A frown emoji can be worth a thousand words: Perceptions of emoji use in text messages exchanged between romantic partners. Issue 8 (December 2017) - Rodrigues, David; Lopes, Diniz; Prada, Marília; Thompson, Dominic; Garrido, Margarida V.
Highlights: Text messaging helps promoting relationship quality. The impact of using emoji in text messages is still unclear. Positive messages were unaffected by adding emoji (Study 1). Negative messages with emoji signaled greater relationship interest (Studies 1–2). In a serious issue, negative messages with emoji signaled less interest (Study 2). Abstract: Computer-mediated communication (CMC) can facilitate the expression of affection between romantic partners and promote relationship quality. Text messaging is nowadays an important means of expressing affection and to feel close to one's partner. However, it is unclear if adding emoji to text messages influences perceptions about the relationship. In two experiments (combined N  = 451), participants evaluated the relationship interest of a romantic partner, based on the messages exchanged. Study 1 compared positive and negative replies varying in emotional cues (without vs. text vs. emoji). Results showed that positive replies signaled the greatest interest, regardless of cue. In contrast, negative replies with (vs. without) cues signaled greater interest in the relationship and this was especially evident for messages with emoji. This benefit occurred because these messages were perceived as more positive (vs. negative messages without cue). Study 2 compared negative replies varying in the seriousness of the issue. Results showed that, for more serious replies, emotional text signaled greater interest by increasing message positivity. In contrast, emoji signaled less interest by increasing message negativity. Together, findings showed how CMC between romantic partners can benefit and be harmed by including emoji.